PRE-SCHOOL CHILDREN OF THE SCIENCE OF INTRODUCTION TO NATURE PLACE IN LIFE - Mamirova Zamira Urakboyevna (Galaxy International Interdisciplinary Research Journal, 2023)
Things in nature consist of two parts: animate and inanimate nature. Inanimate nature includes the earth, sun, moon, stars, water, air, stones, soil, animate plants, animals, microorganisms, and people. The reason why they are called inanimate nature is that they do not feed, do not grow, do not reproduce, do not develop. For example, if we take a stone, it needs neither water nor air. Representatives of living nature cannot live without plants , air, water, light, heat and food, and the most powerful of all creatures in living nature is man.